A DESIGN AND DEVELOPMENT OF ANDROID-BASED LEARNING MEDIA TECHNOLOGY INFORMATION AND COMMUNICATION FOR SENIOR HIGH SCHOOL - Salman Alfarisi Salimu; Fahlul Rizki; Alfina Alfina (Sean Institute, 2022)
This research is motivated by the problem of the limitations of ICT learning resources in Class Ten the even of the academic year 2021/2022. This occurs because of the lack of learning media that attract student interest. Therefore the author seeks to design learning modules that appeal to students. This study aims to determine the validity, practicality, and effectiveness of the Design and Manufacture of learning Media based on Android of Information and Communication Technology Class Ten Even Academic Year 2021/2022. This research and development methods (R&D). The subject of the study amounted to40 people students of Class Ten. This research method using analysis (ADIIE), with design and its development steps, are as follows : (1) Analyze, (2) Design, (3) development, (4) Implementation (5) Evaluate. The validity of the test results by the experts as a whole votes validator test for learning Media based of android of Information and Communication Technology Class Ten Even amounted to 83.03%, so that the level of validity can be interpreted valid to use. Results of the assessment test the practicalities of the overall assessment of the practicalities of Learning Media based on android of Information and Communication Technology Class Ten by 85.94%, so the practical level is very practically used. Results of votes overall effectiveness trials assessing the effectiveness Learning Media based of android of Information and Communication Technology Class Ten by 82.24% so that their effectiveness can be interpreted good used. In conclusion, based on the assessment along with the input of experts and the results of field trials Learning Media based on Android as a learning medium has proven its feasibility, and advantages, and can be used in the learning process on the subjects of computers skills class ten.